THE RELATIONSHIP BETWEEN RELIGIUS AND THE P5 PROGRAM AND PROSOCIAL BEHAVIOR IN STUDENTS - Eldi Mulyana; Erlina Wiyanarti; Bunyamin Maftuh (Journal Civics And Social Studies, 2024)
This research was motivated by the low level of prosocial behavior of students at SMPN 4 Tarogong Kidul. This can be seen from the low level of prosocial behavior among students in terms of sharing, cooperation, helping and honesty. The aim of this research is to determine the relationship between religiosity, the P5 program and prosocial behavior in students at SMPN 4 Tarogong Kidul. The method used in this research is a correlation study with a quantitative approach. The population in this study was 214 class VII students, while the research sample was 100 students using simple random sampling techniques. The data collection techniques used were questionnaires, observation and documentation. The results of this research show that: (1) The description of religiosity, the P5 program and prosocial behavior at SMPN 4 Tarogong Kidul is mostly in the medium category. Based on the results of data analysis, it is known that religiosity is 69%, the P5 program is 69% and prosocial behavior is 71%. (2) There is a positive relationship between religiosity and prosocial behavior in students with a correlation coefficient of 0.337. (3) There is a positive relationship between the P5 program and prosocial behavior in students with a correlation coefficient of 0.497. (4) There is a relationship between religiosity, the P5 program and prosocial behavior in students. These results can be seen from the results of the multiple correlation test which shows that the F Change significance value is 0.000, meaning 0.000 < 0.05, and the correlation coefficient value is 0.510, so it can be concluded that religiosity and the P5 program together with prosocial behavior or simultaneously have a a positive relationship.